A Comparative Study on the Electrodeposition of Tin from Two Different Ionic Liquids: Influence of the Anion on the Morphology of the Tin Deposits. Issue 9 (14th August 2014) - Giridhar, Pulletikurthi; Elbasiony, Amr M.; Zein El Abedin, Sherif; Endres, Frank
Abstract The electrodeposition of tin from two ionic liquids (ILs) containing the 1‐butyl‐1‐methylpyrrolidinium cation ([Py1, 4]+) and the trifluoromethylsulfonate (TfO−) or dicyanamide (DCA−) anion is investigated by cyclic voltammetry, scanning electron microscopy (SEM), infrared (IR) spectroscopy and X‐ray diffraction. Cyclic voltammetry is employed to evaluate the electrochemical behaviour of SnCl2 in the two ILs, and IR spectroscopy is used to study the difference in the complexation of SnCl2 in the two ILs. The electrodeposition of tin is also studied in [EMIm]DCA ([EMIm]+=1‐ethyl‐3‐methylimidazolium), for the purpose of comparison. The morphology of the electrodeposited tin from the different ILs is investigated by SEM, which shows that the morphology of the tin deposits changes upon changing the IL. Agglomerated tin deposits are obtained on gold and copper from [Py1, 4]TfO. Tin dendrites were obtained both from [Py1, 4]DCA and [EMIm]DCA. This study reveals that a change in the ionic composition (anion) of the IL can influence the morphology of electrodeposits of tin and presumably of other elements and compounds.